DESIGN AND IMPLEMENTATION OF AN AI-DRIVEN OBJECT TRACKING ROBOT WITH HUSKY LENS INTEGRATION - Afnan Ahmed,; Verda Tul Zohra,; Ali Mujtaba Durrani,; Abdullah Hidayatullah,; Salman Anjum,; Abdul Subhan,; Syed Junaid Saleem,; Muhammad Shahzaib,; Romaisa Shamshad Khan,; Abdul Aziz, (Spectrum of Engineering Sciences, 2025)
The era of Artificial Intelligence has arrived, with robotics as its most significant application. This paper introduces an object-tracking AI robot programmed to follow a specific object. The robot uses the AI-powered camera HuskyLens to sense and track the objects. The robot is such that it is first trained to learn the object. Once discovered, the robot is able to track and follow the specific object. The HuskyLens senses the object, and the information is passed to the Arduino, which then enables the motors via the motor driver to follow the object. Some existing techniques for controlling object tracking robots are IR sensors, LDR, and RGB sensors. As most of these sensors are not designed for object tracking, these techniques are often not useful enough to meet the requirements of accurately tracking the object. Huskylens, with its AI-powered smart camera alone, can be used as the only sensor in the system to control movement and fulfill the functionality required for object-tracking robots and their various applications.